2019
DOI: 10.4103/apjon.apjon_27_19
|View full text |Cite
|
Sign up to set email alerts
|

Educating Healthcare Employees about Advance Care Planning

Abstract: The objective of this descriptive article is to provide a background of current research and data on advance care planning. Additionally, a proposed and detailed education initiative for increasing completion and understanding of advance care planning documents is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Lastly, the influences of family members on patients's process of ACP decision-making ought to be taken into account by including family members (dyads) in future studies, to reflect the family-bond phenomena in the Chinese culture. The results from our study support nascent efforts to educate health providers in ACPrelated knowledge, to strengthen their communication skills, to provide the ACP-knowledge and skill-set needed to educate patients and their families, and to embrace a multidisciplinary approach-thus ensuring efficient ACPrelated decision-making [55].…”
Section: Conclusion and Recommendationssupporting
confidence: 65%
“…Lastly, the influences of family members on patients's process of ACP decision-making ought to be taken into account by including family members (dyads) in future studies, to reflect the family-bond phenomena in the Chinese culture. The results from our study support nascent efforts to educate health providers in ACPrelated knowledge, to strengthen their communication skills, to provide the ACP-knowledge and skill-set needed to educate patients and their families, and to embrace a multidisciplinary approach-thus ensuring efficient ACPrelated decision-making [55].…”
Section: Conclusion and Recommendationssupporting
confidence: 65%
“…Our sampling strategy also inhibits broad generalizations to other populations; however, we would argue that the present study offers an important contribution to knowledge about the reasoning and considerations leading to prioritized EoL preferences. While the GoWish cards have been used in several recent studies of different contexts and populations ( Banner et al, 2019 ; Delgado-Guay et al, 2016 ; Glennon et al, 2019 ; Kuramoto et al, 2015 ; Zachariah, Klein, Clifton-Hawkins, Andrews, & Gross, 2015 ), we have found few other studies reporting on how GoWish items have been reasoned about and negotiated by users. The study by Lee, Hinderer, and Alexander (2018) on EoL preferences for Chinese Americans is a rare exception, also involving community-dwelling older adults, as they briefly report on how participants commented card items.…”
Section: Discussionmentioning
confidence: 91%
“…Knowledge gaps revealed by the initial findings guided the project team to search for methods of ACP-focused education and narrow the topics that would be taught. 4,6,7,[11][12][13] Change strategies were developed in response to follow-up surveys using the GRiP matrix. 14 This facilitated the group process to explore barriers to best practices and to identify, develop, and implement strategies to increase compliance with audit criteria.…”
Section: Phase 2: Design and Implementation Of Strategies To Improve ...mentioning
confidence: 99%
“…Guided by the literature, the project lead educated the staff regarding AD, Durable Power of Attorney (DPOA), Physicians Orders for Life-Sustaining Treatment (POLST), and Living Wills. 1,7,11 During a virtual meeting with 28 nurses, the project lead delivered a presentation discussing a review of the literature, scope of practice, definitions of common ACP terms, conversation prompts, and policies specific to the medical center. This was recorded, a QR code was made available in the charting room, a weblink was emailed, and 16 additional views were counted.…”
Section: Inadequate Knowledgementioning
confidence: 99%
See 1 more Smart Citation